2016
DOI: 10.1097/md.0000000000004309
|View full text |Cite
|
Sign up to set email alerts
|

Exercise and cancer

Abstract: Background:Colorectal cancer survivors are deconditioned through anticancer therapy. Furthermore, about 10% of them have a permanent ostomy which is associated with weakened abdominal muscles and an increased risk of a hernia. This case study reports on how a firefighter with rectal carcinoma and ostomy was trained to regain operational fitness.Methods:A 44-year-old firefighter (178 cm, 82 kg) with an adenocarcinoma of the rectum (diagnosed 24 months prior) had been treated with neoadjuvant radiochemotherapy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Consistent with other studies investigating the effects of exercise in CRC patients, we also showed improvements in patient-related outcomes, such as QoL as well as emotional and physical functioning. [ 22 , 23 ] Interestingly, the EORTC QLQ-C30 revealed no changes in cancer-related symptom scales, including fatigue, while the FACIT-F revealed a slight improvement in the fatigue subscale. However, it should be noted that the EORTC QLQ-C30 was collected pre- and post-intervention, whereas the FACIT-F was completed prior to the first and last HIIT session.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with other studies investigating the effects of exercise in CRC patients, we also showed improvements in patient-related outcomes, such as QoL as well as emotional and physical functioning. [ 22 , 23 ] Interestingly, the EORTC QLQ-C30 revealed no changes in cancer-related symptom scales, including fatigue, while the FACIT-F revealed a slight improvement in the fatigue subscale. However, it should be noted that the EORTC QLQ-C30 was collected pre- and post-intervention, whereas the FACIT-F was completed prior to the first and last HIIT session.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the integration of exercise into standard clinical care, the most effective way might be a side effects-oriented exercise therapy pathway approach, which includes an initial patient screening with regard to existing symptoms or treatments that are closely linked with symptoms that can be addressed by exercise [20]. This would lead to some kind of standard operation procedures that can be integrated into clinical decision making systems.…”
mentioning
confidence: 99%